Synthesis and Antifungal Studies of (2E)-N-Benzyl-N′-phenylbut-2-enediamide and (2E)-N,N′-Dibenzylbut-2-enediamide Analogues - Habila J. Dama; Kandappa H. Reddy; Patrick Govender; Neil A. Koorbanally (Journal of Chemistry)
A series of eleven butanediamine analogues, of which nine were new, were synthesized by the nucleophilic substitution of aromatic amines and benzylamines with maleic anhydride and tested on four yeast strains of Candida species using the broth microdilution method. Compounds 3a and 3c with an unsubstituted phenyl ring and a 3-methoxyphenyl ring, respectively, are the most active against the fungal species with MIC values ranging from 20.2 to 80.6 μM for C. albicans and C. parapsilosis and 178.5 and 161.2 μM for C. krusei, respectively.